Characterization of Microplastics at Grey Water Wastewater Treatment Plant in South Jakarta City - Panca Hadi Arief Setiawan; Kintan Akila Naurelia; Sandyanto Adityosulindro; Nopa Dwi Maulidiany; Mochamad Adhiraga Pratama (Riviera Publishing, 2025)
Microplastics (MPs) are <5 mm synthetic polymer particles that are emerging contaminants and have been found widely in various water bodies. Wastewater treatment plants (WWTPs) play an important role in containing the release of MPs into the environment, but studies on the effectiveness of greywater-based WWTP, especially in dense urban areas such as Jakarta, are still limited. This research was conducted on a greywater WWTP with Moving Bed Biofilm Reactor (MBBR) technology in South Jakarta to analyze the abundance, efficiency of dispensation, and characteristics of microplastics based on shape, color, size, and material. Samples were taken from five points on weekdays and holidays, analyzed using NOAA methods and FTIR spectroscopy. The abundance of MPs at the inlet reached 942 particles/L (weekdays) and 675 particles/L (holidays), while at the outlet there were 290 particles/L and 211 particles/L, resulting in a dispensing efficiency of 69%. Five types of MPs (foam, fragment, fiber, film, microbead) were found with color variations (white-transparent, yellow, red, blue, green, black), as well as the content of PVFM, PVB, PVA, silicone, and POM polymers. This study contributes to the understanding of the distribution and character of MPs in greywater treatment systems that are still rarely explored, as well as supporting the development of mitigation strategies based on WWTP technology